Medical Teachers’ Perception toward Online Educational Method during Coronavirus Disease 2019 Pandemic - Purvi D Mishra; Shital S Maske; Prathamesh H Kamble (Journal of Medical Academics)
Background: The year 2020 saw the start of the coronavirus disease 2019 (COVID-19) worldwide pandemic. It significantly hindered education but, at the same time, created opportunities for online instruction to improve. This article analyzes the perspectives, preferences, and suggestions of medical teachers regarding online instruction through a questionnaire survey method. Methods: Survey uniform resource locators (URLs) were disseminated via WhatsApp, email, and text messaging to medical teachers in India. The three facets of online teaching—preparation, classroom management, and experiences and recommendations—were assessed. Results: Medical teachers recognized that a methodical approach to setting up and running online live-streaming instruction can positively and significantly impact the quality of teaching and learning. However, teachers concurred that online instruction has a lower overall quality and a smaller learning impact than offline instruction, particularly in practical programs. Approximately, 92.24% of participants stated that offering practical online courses is challenging. Thus, combining online and offline modes for instruction is beneficial. Conclusion: The appropriate use of online education in medical colleges can significantly improve teaching and learning. However, online education cannot replace the effectiveness of the traditional classroom. In future medical education, online teaching can be combined with offline teaching to integrate learning both inside and outside the classroom.